Energy conservation through solar energy assisted dryer for plastic processing industry - Kokate, D.; Kale, D.; Korpale, V.; Shinde, Yogesh; Panse, S.; Deshmukha, S.; Pandit, A. (Elsevier Ltd, 2014)
Consumption of plastics is directly linked with economic growth of plastic industry of respective country. India's plastics consumption is only about 2% of the world. Despite of proposed growth, higher cost of Energy requirement for processing are obstructing growth of plasticulture. Energy efficiency/ conservation measures in plastic processing requires attention to harness alternate energy sources through technological modifications during material processing. This paper depicts practical solution for partial usage of non- conventional energy source; solar energy in conventional plastic process method. About3-5 % of total energy required for processing is utilized for drying and precondition of material. Thus attempt is made to use solar energy for drying of Nylon-6 and polypropylene (PP) by designing natural convection based Solar Dryer. Drying of Nylon-6 is found to be in the falling rate period. Nylon-6 took nearly 6 hrs. (1days) to reach 0.15% moisture content value. Effective diffusivity is varied from 4 - 6.5 X 10-9cm2/sec. Temperature rise for PP material is achieved up to 70°C in the dryer, hence preheating is achieved with same dryer design. Solar dryer can certainly reduce conventional energy consumption during plastic processing at industrial scale. Cost benefit analysis shows that adaptation of solar energy dryer for plastic process industry lead to economic production of plastic goods. © 2014 The Authors.